Effects of Management of Appendicitis with Antibiotics versus Appendectomy in Early Management in Uncomplicated Appendicitis - Sindhu, Shaista; Khatoon, Shahida; Katyar, Ishrat Rahim; Dev, Kapil; Shah, Syed Amir; Asif, Anum (Biological and Clinical Sciences Research Journal, 2025)
Uncomplicated acute appendicitis has traditionally been managed surgically, but recent studies suggest that non-operative management with antibiotics may offer a viable alternative. Evaluating the comparative outcomes of both approaches is crucial for optimizing patient care and resource utilization, especially in resource-constrained settings. Objective: To compare the outcomes of early management of uncomplicated appendicitis with intravenous and oral antibiotics versus laparoscopic appendectomy. Methods: This quasi-experimental study was conducted in the Department of General Surgery at Liaquat University of Medical and Health Sciences (LUMHS), Jamshoro. The sample size was completed in five months from November 2024 to March 2025. A total of 196 patients diagnosed with uncomplicated acute appendicitis were enrolled using consecutive non-probability sampling and equally divided into two groups. Group A (n=98) received intravenous ertapenem (1 g/day) for three days, followed by oral levofloxacin (500 mg once daily) and metronidazole (500 mg thrice daily) for seven days. Group B (n=98) underwent laparoscopic appendectomy. Baseline pain scores were recorded using the Visual Analog Scale (VAS). Patients were reassessed on days 1, 2, and 7 post-intervention for treatment failure, complications, and pain severity. Data were analyzed using SPSS version 25, with chi-square and Mann-Whitney U tests applied where appropriate. A p-value of <0.05 was considered statistically significant. Results: The median age (IQR) of patients was 37 (15) years in Group A and 36 (12) years in Group B. There was no significant difference in hospital stay between the groups (p = 0.239). Treatment failure occurred in 32 patients (32.7%) in the antibiotic group compared to 6 patients (6.1%) in the surgical group (p<0.001). No statistically significant differences were observed between the two groups in terms of postoperative complications (p = 0.172) or VAS pain scores at follow-up (p > 0.05). Conclusion: Laparoscopic appendectomy demonstrated a significantly lower rate of treatment failure compared to antibiotic therapy in patients with uncomplicated acute appendicitis. However, both interventions showed comparable outcomes in terms of hospital stay duration, pain severity, and complication rates. Surgical management remains the more definitive treatment, although antibiotics may be considered in selected cases.